Levothyroxine ‐ not all tablets are the same. Issue 7 (22nd July 2019) - Sohail Siddiqui, Mohsin; Shotliff, Kevin
Abstract : Most patients with hypothyroidism tolerate levothyroxine therapy well, but a significant minority are dissatisfied with treatment. Here, the authors examine whether this could be a result of intolerance to the excipients in the specific levothyroxine product prescribed or dispensed.